Irreversible phase transitions induced by an oscillatory input - López, Alfredo Carlos (2000)
A novel kind of irreversible phase transitions (IPTs) driven by an oscillatory input parameter is studied by means of computer simulations. Second-order IPTs showing scale invariance in relevant dynamic critical properties are found to belong to the universality class of directed percolation. In contrast, the absence of scale invariance is observed for first-order IPTs.